2018
DOI: 10.1111/rda.13381
|View full text |Cite
|
Sign up to set email alerts
|

Effect of semen and donor factors on multiple ovulation and embryo transfer (MOET) in sheep

Abstract: Contents Multiple ovulation and embryo transfer (MOET) is an important tool in the sheep industry for increasing numbers of genetically superior individuals. The objective of this study was to evaluate the effect of semen source (frozen or fresh), the number of embryo collection procedures for each donor (NECP), the season in which embryo transfer and collection was performed, and the age and breed of the donor, on the number of recovered embryos and pregnancy rates after embryo transfer. The Alamos Genetics’ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 33 publications
(54 reference statements)
1
12
0
2
Order By: Relevance
“…This trend follows the natural seasonal regulation of oestrous cycling. Our results are consistent with a recent report describing Dorper sheep embryo transfer (Bergstein‐Galan, Weiss, & Kozicki, ). In that study, the season had a significant effect on the recipient pregnancy rate, with higher pregnancy rates reported in winter (65.57% ± 25.33%) than in spring (37.11% ± 33.27%), summer (29.95% ± 28.33%) or autumn (35.03% ± 31.66%).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This trend follows the natural seasonal regulation of oestrous cycling. Our results are consistent with a recent report describing Dorper sheep embryo transfer (Bergstein‐Galan, Weiss, & Kozicki, ). In that study, the season had a significant effect on the recipient pregnancy rate, with higher pregnancy rates reported in winter (65.57% ± 25.33%) than in spring (37.11% ± 33.27%), summer (29.95% ± 28.33%) or autumn (35.03% ± 31.66%).…”
Section: Discussionsupporting
confidence: 93%
“…Ovine oestrous cycles generally start and end when the day length is decreasing and increasing, respectively. Our results showed that season had a significant effect on pregnancy and live lamb rates, which were significantly higher when embryos were transferred in November-December (winter) than in & Kozicki, 2019). In that study, the season had a significant effect on the recipient pregnancy rate, with higher pregnancy rates reported in winter (65.57% ± 25.33%) than in spring (37.11% ± 33.27%), summer (29.95% ± 28.33%) or autumn (35.03% ± 31.66%).…”
Section: Discussionmentioning
confidence: 64%
“…[1][2][3][4] For these technologies to be efficiently implemented, the number of progeny born from genetically superior females must be maximised. 5,6 Whilst affected by numerous factors, the number of lambs born per donor female are directly related to the viability of transferred embryos. 5 Embryo viability in various species has been found to be affected by embryo developmental stage and quality at the time of transfer, the number of embryos transferred and the type of semen (fresh or frozen-thawed) used for artificial insemination (AI).…”
mentioning
confidence: 99%
“…The embryo collection protocol was followed as Bergstein-Galan et al [ 14 ]. Brifely, donors were sedated with acepromazine 1% (0.05 mg/kg, IM) and inhalation anaesthesia induced with isoflurane.…”
Section: Methodsmentioning
confidence: 99%